Layered scaffolds in periodontal regeneration - Niloufar Abedi; Negar Rajabi; Mahshid Kharaziha; Farahnaz Nejatidanesh; Lobat Tayebi (Elsevier, 2022)
Periodontitis is a common inflammatory disease in dentistry that may lead to tooth loss and aesthetic problems. Periodontal tissue has a sophisticated architecture including four sections of alveolar bone, cementum, gingiva, and periodontal ligament fiber; all these four can be damaged during periodontitis. Thus, for whole periodontal regeneration, it is important to form both hard and soft tissue structures simultaneously on the tooth root surface without forming junctional epithelium and ankylosis. This condition makes the treatment of the periodontium a challenging process. Various regenerative methods including Guided Bone/Tissue Regeneration (GBR/GTR) using various membranes have been developed. Although using such GBR/GTR membranes was successful for partial periodontal treatment, they cannot be used for the regeneration of complete periodontium. For this purpose, multilayered scaffolds are now being developed. Such scaffolds may include various biomaterials, stem cells, and growth factors in a multiphasic configuration in which each layer is designed to regenerate specific section of the periodontium. This article provides a comprehensive review of the multilayered scaffolds for periodontal regeneration based on natural or synthetic polymers, and their combinations with other biomaterials and bioactive molecules. After highlighting the challenges related to multilayered scaffolds preparation, features of suitable scaffolds for periodontal regeneration are discussed.